Immobilization of blood coagulant factor VII on polycaprolactone membrane through polydopamine grafting - Gopal, Rathosivan; Md Shakhih, Muhammad Faiz; Sahalan, Mariaulpa; Lee, Te Chuan; Hermawan, Hendra; Sivalingam, Sivakumar; Kadiman, Suhaini; Saidin, Syafiqah (Elsevier, 2023)
Postoperative bleeding following cardiac surgeries is still an issue that deranges the medical resources and cost. The oral and injection administrations of blood coagulation protein, Factor VII (FVII), is effective to stop the bleeding. However, its short half-life has limited the effectiveness of this treatment and frequent FVII intake may distress the patients. Instead, incorporating FVII into synthetic biodegradable polymers such as polycaprolactone (PCL) that is commonly used in drug delivery applications should provide a solution. Therefore, this study aimed to immobilize FVII on PCL membranes through a cross-linkage polydopamine (PDA) grafting as an intermediate layer. These membranes are intended to provide a solution for cardiac bleeding in coagulating blood and sealing the sutured region. The membranes were evaluated in terms of its physio-chemical properties, thermal behavior, FVII release profile and biocompatibility properties. The ATR-FTIR was used to analyze the chemical functionalities of the membranes. Further validation was done with XPS where the appearances of 0.45 ± 0.06% sulfur composition and C–S peak have confirmed the immobilization of FVII on the PCL membranes. The cross-linked FVIIs were viewed in spherical immobilization on the PCL membranes with a size range between 30 and 210 nm. The surface roughness and hydrophilicity of the membranes were enhanced with a slight shift of melting temperature. The PCL-PDA-FVII0.03 and PCL-PDA-FVII0.05 membranes, with wide area of FVII immobilization released approximately only 22% of FVII into the solution within 60 days period and, it is found that the PCLPDA-FVIIx membranes projected the Higuchi release model with non-Fickian anomalous transport. While the cytotoxic and hemocompatibility analyses showed advance cell viability, identical coagulation time and low hemolysis ratio on the PCL-PDA-FVIIx membranes. The erythrocytes were viewed in polyhedrocyte coagulated structure under SEM visualization. These results validate the biocompatibility of the membranes and its ability to prolong blood coagulation, thus highlighting its potential application as cardiac bleeding sealant.